2012
DOI: 10.1002/j.1875-9114.2012.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from a Mentored Research Boot Camp: Focused Investigator Training (FIT) Program

Abstract: The FIT Program was associated with a significant increase in attendees' self-efficacy for obtaining external research funding. Program attendance was associated with numerous successfully funded grants by pharmacist investigators. Future FIT Program success hinges on attracting adequate numbers of qualified applicants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In the United States, the National Institute of Health has strongly endorsed the role of the clinical pharmacist as an investigator, and there has been a substantial increase in pharmacist-directed research, as shown by the growth in funded grants and scientific publications [ 15 ]. The American College of Clinical Pharmacy (ACCP) Research Institute conducted a Mentored Research Boot Camp, Focused Investigator Training (FIT) Program, and reported that this program was associated with a significant increase in attendees’ self-efficacy in obtaining external research funding [ 16 ]. Overholser et al [ 17 ] reported that taking a two-credit elective course in clinical research increased pharmacy students’ interest in pursuing a career in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the National Institute of Health has strongly endorsed the role of the clinical pharmacist as an investigator, and there has been a substantial increase in pharmacist-directed research, as shown by the growth in funded grants and scientific publications [ 15 ]. The American College of Clinical Pharmacy (ACCP) Research Institute conducted a Mentored Research Boot Camp, Focused Investigator Training (FIT) Program, and reported that this program was associated with a significant increase in attendees’ self-efficacy in obtaining external research funding [ 16 ]. Overholser et al [ 17 ] reported that taking a two-credit elective course in clinical research increased pharmacy students’ interest in pursuing a career in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a survey of ACCP members found that approximately two-thirds of respondents working in positions with heavy research responsibilities did not have formal research training. 20 While many individuals have been very successful in their research career despite minimal formal training, the question remains about the best way to meet these educational needs of trainees.…”
Section: Postgraduate Training: Fellowship and Residencymentioning
confidence: 99%
“…5 Postgraduate Year Two (PGY2) accreditation standards vary whether conduction of a research project is explicitly required. 6 However, many pharmacists enter positions where scholarly activity is expected with only PharmD and one or two years of residency training to teach current residents numerous skills required to conduct practice-based research 7–10 which can lead to a cycle of inadequately trained pharmacists training future residents. 11 Description and quantification of the resident research training experience aids in residency program improvement, comparison, and promotion.…”
Section: Introductionmentioning
confidence: 99%